2022-RA-1638-ESGO Randomized phase III trial on Niraparib-TSR-042 (dostarlimab) versus physician's choice in recurrent ovarian, fallopian tube, or primary peritoneal cancer patients not candidate for platinum retreatment: NItCHE trial (MITO 33). (20th October 2022) - Salutari, Vanda; Musacchio, Lucia; Pignata, Sandro; Braicu, Elena; Cibula, David; Colombo, Nicoletta; Frenel, Jean Sebastien; Giolitto, Serena; Camarda, Floriana; Perri, Maria Teresa; Giudice, Elena; Scambia, Giovanni; et al.
Abstract : Introduction/Background: Platinum resistant ovarian cancer patients have a poor prognosis, and few treatment options are available. Preclinical and clinical data demonstrated that the combination of poly-ADP ribose polymerase inhibitors (PARPi) with immune checkpoint inhibitors (ICIs) could have a synergistic antitumor activity in this setting of patients. MITO 33 trial will assess the hypothesis that the combination niraparib/dostarlimab therapy is effective in increasing overall survival, progression free survival and time to first subsequent therapy with respect to chemotherapy alone. Methodology: Patients will be randomized 1:1 to receive:Arm A (physician's choice chemotherapy): pegylated liposomal doxorubicin 40 mg/mq d1q28, weekly paclitaxel 80 mg/mq d1, 8, 15q28, gemcitabine 1000 mg/mq d1, 8, 15q28 or topotecan 1.25 mg/mq d1–5q21;Arm B (dostarlimab + niraparib): dostarlimab 500 mg every 3 weeks for 4 cycles, then 1000 mg every 6 weeks + niraparib 300 mg or 200 mg daily.Patients will be stratified according to homologous recombination deficiency status (positive vs negative), PD-L1 status, previous immunotherapy, previous PARPi treatment and Bevacizumab therapy. Homologous Recombination Deficiency status will be evaluated with Foundation One CDx test and tumor PD-L1 expression will be evaluated on archival pre-therapy lesion. Results: Inclusion Criteria - Recurrent platinum resistant epithelial ovarian, fallopian tube or primary peritoneal cancer (no more than 2 previous chemotherapy lines)- Previous treatment with PARPi and/or ICIs are allowed (if at least 6 months from last treatment have intercurred)- Conclusion: Primary Endpoint: Overall SurvivalSecondary Endpoints: Progression Free Survival; Time to First Subsequent Therapy and Objective Response Rate; Safety and Tolerability of Dostarlimab plus Niraparib